2008
DOI: 10.1007/s11540-008-9120-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of the Potato: New Insights into Root System and Repercussions for Crop Management

Abstract: Potato roots are concentrated mostly in the plow layer up to 30 cm in soil depth. Some roots extend up to 100 cm depth and the total root length throughout the soil profile reaches about 10-20 km m −2 area. There are large differences in root mass (dry weight and length) in the plow layer between cultivars, breeding lines and wild relatives. The differences are generally stable across different environmental conditions, such as locations with different soil types, fertilizer rates and planting densities. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
118
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(136 citation statements)
references
References 32 publications
15
118
1
2
Order By: Relevance
“…The root surface area showed the same distribution. Many studies found a positive relationship between the size of the root system and the amount of aboveground biomass (Iwama 2008, Rykaczewska 2015. In our research a dependence was also observed, but these correlations were not statistically significant.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…The root surface area showed the same distribution. Many studies found a positive relationship between the size of the root system and the amount of aboveground biomass (Iwama 2008, Rykaczewska 2015. In our research a dependence was also observed, but these correlations were not statistically significant.…”
Section: Discussioncontrasting
confidence: 62%
“…The root systems were measured when the plants were in full vegetation (blooming), in the third week of June, as the previous study found that potato plants show the largest differences in the size of the root system (Iwama 2008).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In natural conditions, the root growth of potato plants decreases 40 to 50 days after emergence (stage of expansion and maturity of the tuber), and this has to do with the translocation of assimilates of the root towards the tubers in formation (Rousselle & Robert, 1996;Iwama, 2008). In this study, the reduction in the percentage of the length of the root in regard to the control is attributed to the osmotic and toxic stress induced by each one of the salinities primordially in EC > 3.88 dS m -1 .…”
Section: Root Lengthmentioning
confidence: 99%